Characterization of fungal pathogens and germplasm screening for disease resistance in the main production area of the common bean in Argentina - Taboada, Gisel; Abán, Carla L.; Mercado Cárdenas, Guadalupe; Spedaletti, Yamila; Aparicio González, Mónica; Maita, Efrain; Ortega-Baes, Pablo; Galván, Marta (Frontiers in Plant Science, 2022)
Common bean (Phaseolus vulgaris L.) is the most important grain legume in a human diet, principle in Africa and Latin America. Argentina is one of the five major producers of common bean in the world, and the main cultivated areas are concentrated in the northwestern provinces of this country. Crop production of common bean is often affected by biotic factors like some endemic fungal diseases, which exert a major economic impact on the region. The most important fungal diseases affecting common bean in Argentina are white mold (caused by Sclerotinia sclerotiorum), angular leaf spot (caused by Pseudocercospora griseola), web blight and root rot (caused by Rhizoctonia solani), which can cause production losses of up to 100% in the region. At the present, the most effective strategy for controlling these diseases is the use of genetic resistance. In this sense, population study and characterization of fungal pathogens are essential for developing cultivars with durable resistance. In this review we report diversity studies carried out on these three fungal pathogens affecting common bean in northwestern Argentina, analyzing more than 200 isolates by means of molecular, morphological and pathogenic approaches. Also, the screening of physiological resistance in several common bean commercial lines and wild native germplasm is reviewed. This review contributes to the development of sustainable management strategies and cultural practices in bean production aimed to minimize yield losses due to fungal diseases in common bean.